2022
DOI: 10.3390/nu14245330
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Mechanism of Polysaccharides in Anti-Aging

Abstract: The elderly proportion of the population is gradually increasing, which poses a great burden to society, the economy, and the medical field. Aging is a physiological process involving multiple organs and numerous reactions, and therefore it is not easily explained or defined. At present, a growing number of studies are focused on the mechanisms of aging and potential strategies to delay aging. Some clinical drugs have been demonstrated to have anti-aging effects; however, many still have deficits with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Aging is a progressive and irreversible functional decline involving multiple organs and numerous responses that occur in all organisms [ 88 ]. GAG is primarily located in the extracellular matrix and is synthesized via fibroblasts within dermal cells.…”
Section: Biological Activities Of Animal Polysaccharidesmentioning
confidence: 99%
“…Aging is a progressive and irreversible functional decline involving multiple organs and numerous responses that occur in all organisms [ 88 ]. GAG is primarily located in the extracellular matrix and is synthesized via fibroblasts within dermal cells.…”
Section: Biological Activities Of Animal Polysaccharidesmentioning
confidence: 99%
“…In this regard, it is worth highlighting that most of the studies conducted to date on in vitro and in animal models that demonstrate the neuroprotective properties of mushrooms have been conducted on mushroom polysaccharides [169] (Table 1).…”
Section: Antioxidant Compounds Of Mushrooms As Neuroprotective Agentsmentioning
confidence: 99%
“…It has been reported that mushroom antioxidant compounds, due to their ability of increasing antioxidant defenses and counteract oxidative stress, may prevent age-related neurological diseases [165][166][167][168] (Figure 7). In this regard, it is worth highlighting that most of the studies conducted to date on in vitro and in animal models that demonstrate the neuroprotective properties of mushrooms have been conducted on mushroom polysaccharides [169] (Table 1).…”
Section: Antioxidant Compounds Of Mushrooms As Neuroprotective Agentsmentioning
confidence: 99%
“…The decreased ability of adult stem cell populations to proliferate and regenerate is one of the main causes of the human ageing process [ 5 ]. Current anti-ageing drugs exhibit potent anti-ageing effects; however, some drawbacks remain regarding their safety and long-term use [ [9] , [10] , [11] ]. Therefore, it is necessary to find anti-ageing drugs that are not only safe and effective for longer usage periods.…”
Section: Introductionmentioning
confidence: 99%